Cassava Processing and Digital Marketing Training in Kepanjenlor Village, Blitar City - Nabila Adelia; Budi Prabowo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The rapid development of changing has resulted in increasing the growth and use of the internet on a global scale. Digital marketing is a marketing medium that currently in great demand by the public to support various activities. Several MSMEs in Kepanjenlor Subdistrict, Blitar City are still not utilizing digital marketing due to the lack of literacy, online marketing training, and conventional sales. The aim of this activity is to help overcome this problem by increasing wider marketing of MSME businesses in Kepanjenlor Subdistrict, Blitar City, especially in RT 01 RW 05. As a result of this activity, participants can obtain information and develop business opportunities.